Impact of Climate Change on the Emergence and Decline of Ancient Civilizations-Historical Climate Reconstruction from Earth Science Perspectives - Dai, Qixin (Transactions on Environment, Energy and Earth Sciences, 2024)
The impact of climate change on ancient civilizations is an important research topic. Ancient societies were extremely dependent on natural resources and climatic conditions due to their constraints, and climate fluctuations often had far-reaching impacts on agricultural production, resource management, and social stability of ancient civilizations. The aim of this paper is to investigate the impact of climate change on ancient civilizations using geoscientific reconstruction of historical climate. The study includes an analysis of the information provided by ice core data and sediments, and then describes how climate change affected ancient civilizations from different perspectives. In addition, the essay summarizes how modern geosciences and technology have provided useful tools for related research fields. Through historical climate reconstruction, this paper deepens the understanding of how historical climate change affected ancient civilizations and provides valuable lessons for other researchers to follow.